Bimbingan Teknis Kompetensi Manajemen Proyek Untuk Kompetensi Tambahan Calon Lulusan Universitas Iqra Buru - Fauzan A. Sangadji (Yayasan Literasi Sains Indonesia, 2023)
A construction project is one of the activities in which the results of the work are affected by the productivity of the workforce. Activities in construction projects are interrelated, so that if one activity is hampered it will hinder other activities in the field. Likewise construction activities are complex jobs and require more attention in their implementation. The elements that are part of the construction are cost, quality, and time in which there are also resources that must be controlled, such as work and materials. Based on this, it is necessary to have technical guidance for prospective civil engineering graduates to prepare them so that they are better prepared and able to enter the world of construction work later. Based on this, the Ministry of PUPR, the Director General of Construction Development, Jayapura Region VII Construction Services Center, and Iqra University, work together to carry out technical assistance activities in the Auditorium Room of Iqra Buru University, Namlea Regency. This activity lasted for 3 days. There were several materials presented, namely Project Management, K3, Quality Control and Precast Concrete. The activity participants consisted of more than 30 students, the majority of whom were final students who were doing their thesis and were about to graduate. This activity is carried out with lectures, giving assignments and questions and answers. This is done so that students are more focused on listening to the material and activities that are taking place.